Salivarian Trypanosomosis: A Review of Parasites Involved, Their Global Distribution and Their Interaction With the Innate and Adaptive Mammalian Host Immune System - Radwanska, Magdalena; Vereecke, Nick; Deleeuw, Violette; Pinto, Joar; Magez, Stefan (Frontiers in Immunology, 2018)
Salivarian trypanosomes are single cell extracellular parasites that cause infections in a wide range of hosts. Most pathogenic infections worldwide are caused by one of four major species of trypanosomes including (i) Trypanosoma brucei and the human infective subspecies T. b. gambiense and T. b. rhodesiense, (ii) Trypanosoma evansi and T. equiperdum, (iii) Trypanosoma congolense and (iv) Trypanosoma vivax. Infections with these parasites are marked by excessive immune dysfunction and immunopathology, both related to prolonged inflammatory host immune responses. Here we review the classification and global distribution of these parasites, highlight the adaptation of human infective trypanosomes that allow them to survive innate defense molecules unique to man, gorilla, and baboon serum and refer to the discovery of sexual reproduction of trypanosomes in the tsetse vector. With respect to the immunology of mammalian host-parasite interactions, the review highlights recent findings with respect to the B cell destruction capacity of trypanosomes and the role of T cells in the governance of infection control. Understanding infection-associated dysfunction and regulation of both these immune compartments is crucial to explain the continued failures of anti-trypanosome vaccine developments as well as the lack of any field-applicable vaccine based anti-trypanosomosis intervention strategy. Finally, the link between infection-associated inflammation and trypanosomosis induced anemia is covered in the context of both livestock and human infections.